2021
DOI: 10.1002/ange.202013561
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Under Reductive Conditions: From Benzylic Ethers to Acetals with Perfect Atom‐Economy by Titanocene(III) Catalysis

Abstract: Described here is atitanocene-catalyzed reaction for the synthesis of acetals and hemiaminals from benzylic ethers and benzylic amines,r espectively,with pendant epoxides.T he reaction proceeds by catalysis in single-electron steps.T he oxidative addition comprises an epoxide opening.AnH-atom transfer,t og enerate ab enzylic radical, serves as ar adical translocation step,a nd an organometallic oxygen rebound as ar eductive elimination. The reaction mechanism was studied by high-level dispersion corrected hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The investigation of photocatalysts suggested other organic fluorophores such as 4CzIPN, 4DPAIPN, and 5CzBN resulted in inferior yields of 3 aa (entries 2–4). Ti catalysts with either different counterions (Cp 2 TiBr 2 , Cp 2 Ti(OTf) 2 , Cp 2 Ti(OMs) 2 , and Cp 2 Ti(TFA) 2 ) [21e,g] or different ligands (Cp*TiCl 3 and Ti(O i ‐Pr) 4 ) afforded 3 aa in lower yields than Cp 2 TiCl 2 (entries 5–10). Reactions in THF and DMF did not work so well as that in DCE (entries 11 and 12).…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of photocatalysts suggested other organic fluorophores such as 4CzIPN, 4DPAIPN, and 5CzBN resulted in inferior yields of 3 aa (entries 2–4). Ti catalysts with either different counterions (Cp 2 TiBr 2 , Cp 2 Ti(OTf) 2 , Cp 2 Ti(OMs) 2 , and Cp 2 Ti(TFA) 2 ) [21e,g] or different ligands (Cp*TiCl 3 and Ti(O i ‐Pr) 4 ) afforded 3 aa in lower yields than Cp 2 TiCl 2 (entries 5–10). Reactions in THF and DMF did not work so well as that in DCE (entries 11 and 12).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ring opening of dibenzyl ether 1AG produced alcohol 2AG along with benzylidene acetal 4AG obtained in the previous titanocene-mediated ring opening via 1,5-hydrogen atom transfer (HAT). 36 In addition to trisubstituted epoxides (1AH-1AJ), natural product-derived epoxides (1AK-1AN) could also be readily opened in good yields. Comparisons to the analogous precedents performed by titanocene highlighted the reverse reactivity in ring opening.…”
mentioning
confidence: 99%
“…DFT calculations indicated that ring opening with titanocene was endothermic, which is consistent with a previous study. 36 Since titanocene-bounded tertiary radical IIb is more stable than the corresponding primary radical IIa by 6.82 kcal/mol, ring opening under thermodynamic control results in a large abundance of IIb which undergoes HAT to afford IIIb as a major product. In contrast, ring opening with zirconocene was found to be extremely exothermic and practically irreversible.…”
mentioning
confidence: 99%